Intrathecal clonidine for post-operative pain relief in lower abdominal surgeries - Lele, Smita S.; Rupwate, Kanchan R.; Minhas, Reepmala; Tendolkar, Bharati (International Journal of Research in Medical Sciences, 2016)
Background: Spinal anaesthesia is preferred method for surgeries of lower half of the body due to its efficacy, rapidity, minimal side effects. Generally bupivacaine is given as an spinal anaesthetic agent because of its analgesic effect in the initial postoperative period. For additional analgesic effect particularly for lower limb surgeries now-a-days it is recommended to add an adjuvant inj.clonidine. Hence the present study is aimed to compare the effects of combination of clonidine with bupivacaine and bupivacaine alone. Methods: The study was prospective, randomized, double blinded and controlled study. 90 indoor patients between age group of 18-70 years of either sex of ASA physical status I/II who were to undergo lower abdominal surgeries including gynaecological, orthopaedic and surgical were selected for the study. Parameters like post operative analgesic effects, onset, peak level and two segment regression of sensory block and onset, peak and recovery of motor block, time of rescue analgesia and various side effects were assessed on administration of clonidine at a dose 60 mcg intrathecally and 75 mcg of bupivacaine and comparing the same with bupivacaine hydrochloride alone. Results: Of 90 patients, the mean age group of the patients was 34, mean weight was 56 kgs and average height was 106 cm. The number of males was 63 and females were 27. Patients receiving bupivacaine 0.5% and different doses of clonidine 60 mcg and 75 mcg (group B and group C) respectively produced significant sensory and motor blockade, increases in time of rescue analgesic with lesser side effects compared to bupivacaine alone receiving group. When compared group B and group C, group receiving highest dose of clonidine produced good results compared to group B. Conclusions: It is concluded that patients receiving bupavacaine with clonidine at different doses produced significant anaesthetic, analgesic effect and lesser side effects compared to bupavacaine alone receiving group.